Prevalence and Determinants of Vitamin D Deficiency during the First Trimester: Evidence from a Major Metropolitan City in Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2024)
Introduction: Vitamin D deficiency in early trimesters can have detrimental effect on feto-maternal outcomes. This research aimed to determine the prevalence  and possible associated factors with vitamin D deficiency during first trimester in Chattogram city, Bangladesh.Methods: This was a cross-sectional study conducted from July to September, 2023 in Chattogram metropolitan city with purposive sampling. After obtaining consent a questionnaire was provided and blood was drawn for biochemical analysis. Statistical inference was done through SPSS V25.Results: Total 398 women participated in this study with mean age of 27 years. More than half (51.8%) were suffering subpar vitamin D level, with 15.1% being deficient and 36.7% having insufficient vitamin D level. Most participants were housewives (78.6%) with over half (57.5%) completing their undergraduate degree. Private service (40.5%) was the most prevalent spouse’s profession. Most of the women were primigravid (41.2%). 34.4% and 34.4% of participants had one instance of cesarean section and abortion respectively. High prevalence of anemia was present (49.2%) and was statistically significant with subpar vitamin D level (p